Experiences in the school library usage as a guideline for planning information literacy programmes: with special reference to the new entrants of LLB programme at University of Peradeniya - Wijetunge, Pradeepa (My University, 2015)
The paper discusses the prior experiences of the use of a library in the stream of Law by new entrants of University of Peradeniya in 2015. Survey research strategy was used with a structured questionnaire administered for the new intake of the Department of Law at the point of registration in the library. Out of the total of 56, 38(68%) responded. Of the respondents, 94.7% have been asked by their teachers to read material other than the classroom notes, 97.4 have borrowed books from their school library but only 37.8% have used magazines and 81.6% have studied in the school library, 48.6% confirmed that they had a catalogue but 66.7% did not have computers in the library. They have secured reading material required from the library, from friends and relatives. In response to their access to email and social media, 64.9% confirmed that they have email, but the use of other media (Face book, skype and twitter, are not common) but 70.3% have a smart phone and 83% have expressed that they would like to receive SMS from the university library. Based on these findings it is recommended that the training for new entrants must provide more training on the use of journals, online and card catalogues and computers to search and retrieve information. It is also recommended to design the communication channels through email and social media as the majority of the students like to communicate with the university library through these media.
Keywords: New Entrants, Undergraduates, School Library, Social Media, University of Peradeniya, Law